Phenomenon of Cancel Culture Applied at Film Adaptation ‘A Business Proposal’ - Aliftya Darinda Naminputri (al-Afkar, Journal For Islamic Studies, 2026)
This research is analyzing the phenomenon of Korean’s cancel culture that applied in Indonesia for the film adaptation of 'A Business Proposal' (2025) which caused the failure of this film since the first day of airing. This study aims to examine the causes and implementation of cancel culture in X which has an impact on Indonesian films. This research uses a qualitative approach with a case study method of cancel culture for the film adaptation of A Business Proposal. Data collection techniques carried by documenting netizen opinions from X, observation, and literature studies. This research refers to Social Control Theory. This research results that cancel culture is carried out because the actors don't study the original characters, statements of fanatic fans, Abidzar claimed to receive racist treatment, don't mind about netizen comments, Abidzar and Ariel said 'don't watch the film', Caitlin's wrong statement. Cancel culture in social media X are carried out by announcement at the big community in X, tracing Abidzar's background as a son of Indonesia’s great Ustaz, stating cancel to large X’s accounts, reporting empty seats in several cinemas, stating cancel with making jokes and memes.